PEMANFAATAN DAN EFISIENSI KURKUMIN KUNYIT (CURCUMA DOMESTICA VAL) SEBAGAI INDIKATOR TITRASI ASAM BASA - Ratna Sundari (Teknoin, 2016)
The composition of the turmeric plant consists of a root, rhizome, pseudostem, stem leaf, leaves, flower stalks and flowers.Chemical substances contained in turmeric is essential oil, starch, fiber and ash. Turmeric chemical content will be higher if it comes from the lowland compared with turmeric, which comes from the highlands.Curcumin is coloring agentto orange yellow crystalline, insoluble in ether, soluble in oils, alkali maroon, while the bright yellow acid. pH indicator is an organic acid or base having one color if the hydrogen concentration is higher than at a certain price and a color if the concentration was lower. The analysis shows that the optimum extraction temperature is 70 0C, with the extraction time of 120 minutes, the particle size of 100 mesh.Concentration yield is curcumin produced 5.158 mg / L. The cost efficiency of the use of curcumin indicator reached 27,7%.